2011
DOI: 10.1002/ejlt.200900231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural antioxidants on the formation of trans‐fatty‐acid isomers during heat treatment of sunflower oil

Abstract: The intake of foods containing trans fatty acids (TFAs) can have deleterious effects on human health, mainly on the cardiovascular system. Thus, it is important to consider the processes that form TFAs in foods, and the alternatives to minimise their formation. The influence of two added natural antioxidants on TFA formation during heat treatment (120 h at 1808C) of sunflower vegetable oil were examined: rosemary extract (Rosmarinus officinalis L.) (1 g per kg oil) and lutein (0.1 g per kg oil). Changes in FA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…The content of linolenic acid decreased with frying time. There was not a significant difference between sunflower and rosemary extract containing sunflower oil in terms of fatty acid distribution as was also previously reported by Filip et al, (2011).…”
Section: Fatty Acid Composition Of Frying Oilssupporting
confidence: 85%
See 2 more Smart Citations
“…The content of linolenic acid decreased with frying time. There was not a significant difference between sunflower and rosemary extract containing sunflower oil in terms of fatty acid distribution as was also previously reported by Filip et al, (2011).…”
Section: Fatty Acid Composition Of Frying Oilssupporting
confidence: 85%
“…The changes in fatty the acid composition of the frying oil during repeated frying are given in Table 4. Sunflower oil showed a typical fatty acid composition including 56.89% linoleic, 34.03% oleic, 5.97% palmitic and 2.91% stearic acids as is common for most sunflower oils (Sánchez-Gimeno et al, 2008;Filip et al, 2011). There was an obvious reduction in linoleic acid, with a consequent increase in the contents of oleic acid and palmitic acids as reported by Romero et al, (2000) and Casal et al, (2010).…”
Section: Fatty Acid Composition Of Frying Oilsmentioning
confidence: 62%
See 1 more Smart Citation
“…Ramolho and Jorge reported that soybean oil supplemented with rosemary extract had 7.99% total polar material content, while non‐supplemented control had 17.35% polar material content at the end of a 10 h heating period at 180 °C. In another study, Filip et al showed that sunflower oil containing rosemary extract and lutein had less polar material than control samples during heat treatment at 180 °C for 120 h.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, rosemary is the most commonly used plant for preventing lipid oxidation and has a high antioxidant activity . Carnosol, carnosic acid, and rosmarinic acid are the most important components in rosemary extracts . Essential oil of rosemary also contains components such as 1,8‐cineole, α‐pinene, camphene, and β‐pinene .…”
Section: Introductionmentioning
confidence: 99%